2020
DOI: 10.1093/mnras/staa1479
|View full text |Cite
|
Sign up to set email alerts
|

Shapes and alignments of dark matter haloes and their brightest cluster galaxies in 39 strong lensing clusters

Abstract: ABSTRACT We study shapes and alignments of 45 dark matter (DM) haloes and their brightest cluster galaxies (BCGs) using a sample of 39 massive clusters from Hubble Frontier Field (HFF), Cluster Lensing And Supernova survey with Hubble (CLASH), and Reionization Lensing Cluster Survey (RELICS). We measure shapes of the DM haloes by strong gravitational lensing, whereas BCG shapes are derived from their light profiles in Hubble Space Telescope images. Our measuremen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 83 publications
2
29
0
Order By: Relevance
“…tighter alignment than that reported by Durret et al (2019), who found an alignment for 12 out of 21 BCGs (57%) between redshifts 0.21 and 0.89. Okabe et al (2020) study the alignment of 45 dark matter (DM) haloes and their BCGs up to z = 0.97, and find that BCGs tend to be well aligned with their DM haloes, with a mean difference of 22.2 ± 3.9 • . A similar study was done by Ragone-Figueroa et al (2020) on the alignment of BCGs both with the distribution of cluster galaxies and DM haloes, by analyzing cosmological hydro-simulations of 24 clusters.…”
Section: Discussionmentioning
confidence: 99%
“…tighter alignment than that reported by Durret et al (2019), who found an alignment for 12 out of 21 BCGs (57%) between redshifts 0.21 and 0.89. Okabe et al (2020) study the alignment of 45 dark matter (DM) haloes and their BCGs up to z = 0.97, and find that BCGs tend to be well aligned with their DM haloes, with a mean difference of 22.2 ± 3.9 • . A similar study was done by Ragone-Figueroa et al (2020) on the alignment of BCGs both with the distribution of cluster galaxies and DM haloes, by analyzing cosmological hydro-simulations of 24 clusters.…”
Section: Discussionmentioning
confidence: 99%
“…We also use the large-area low-resolution lens model produced by Merten et al (2011) in MACS0416 and MACS1149, where the identified sources are out of the coverage of the CATS products. For sources detected in the CLASH and RELICS cluster fields, we use all of the available lens models on the MAST high-level science product database, including those produced by CATS (Richard et al 2014), Zitrin-dPIEeNFW andLight-Traces-Mass (Zitrin et al 2013, 2015), and GLAFIC (Oguri 2010;Kawamata et al 2016;Okabe et al 2020).…”
Section: Lens Models and Magnificationmentioning
confidence: 99%
“…We also use the large-area low-resolution lens model produced by Merten et al (2011) in MACS0416 and MACS1149, where the identified sources are out of the coverage of the CATS products. For sources detected in the CLASH and RELICS cluster fields, we use all of the available lens models on the MAST high-level science product database, including those produced by CATS (Richard et al 2014), Zitrin-dPIEeNFW and Light-Traces-Mass (Zitrin et al 2013(Zitrin et al , 2015, and GLAFIC (Oguri 2010;Kawamata et al 2016;Okabe et al 2020).…”
Section: Lens Models and Magnificationmentioning
confidence: 99%